Banning Novels at Schools in Indonesia: An Investigation of Education Policy Execution - Lestari Budianto; Iwan Hadi; Siti Zulaiha; Noer Aisyah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Novel is one of the literary works that people like to read for several reasons. The readers are not only adults but also teenagers and children. Novels can be a good source of knowledge for everyone including students. Reading novels can give many positive impacts in terms of language and emotions. However, the existence of novels is banned at some schools in Indonesia. The banning is based on several reasons. This paper investigated the perspectives of students and teachers related to the banning of novels in a school in Indonesia. This research used a descriptive qualitative design. The data were collected through semi-structured interviews with students and teachers at the school. The result showed that there were several problems related to the use of the novels in terms of kinds and the reading time of the novels. However, the use of novels is also beneficial in terms of emotion, habits, and knowledge. Considering the advantages and the disadvantages of novels at school, this research provided suggestions related to the ban of novels in terms of kinds of novels and reading time.